Management of maxillofacial trauma in prisoners. Issue 4 (May 2019) - Clark, M.; Mitchell, O.; Downie, I.
Abstract: The incidence of injuries among prisoners is much higher than in the general population, and in the UK the number of prisoners and the incidence of injuries are rising. Maxillofacial trauma is common. Based on the cases of 12 patients, we have identified eight challenges that are associated with the management of maxillofacial trauma in this group: patient-reported mechanisms of injury that are often inconsistent with the fracture pattern, complex fracture patterns, delayed presentation, high prevalence of dental disease and of smoking, complicating medical factors such as drug use and blood-borne viruses, increased risk of further violence after discharge, and problems with follow-up logistics. By actively addressing these challenges we can provide a better service to these patients.